Weak Motivation to learn Arabic in the New Normal Life/ضعف دافعية تعلم اللغة العربية في الحياة الطبيعية الجديدة - Zulfa, Akhmad (Jurnal Al-Maqoyis, 2021)
The Covid-19 emergency outbreak was imposed by the Indonesian government, and the minister of education launched a study from home since March 2020. Learning is done online / in accordance with government regulations to break the spread of the epidemic. Then at the present time after going through the difficult times of the covid-19 pandemic, we are faced with a transition period before this outbreak ends which is known as the new normal which is required to get used to online learning. This study aims to reveal the problem of demotivating Arabic learning that occurs at Madrasah Tsanawiyyah 1 and 2 in district Gambut province south kalimantan. This study used a descriptive qualitative method and the research approaches used case study. The research sample was selected using purposive sampling technique, and the research data were obtained through observation and interviews. The results showed that (1) of the 10 types of motivation proposed by Harmer (2001), only 4 types of demotivation were experienced by students in learning Arabic at Madrasah Tsanawiyyah 1 and 2 in district Gambut province south kalimantan, that is demotivative because of conflict of values, demotivative because of lack of confidence, demotivative because of isolation, demotivative because of boredom.